Development of the Mafriwal dairy cattle of Malaysia - Panandam, J.M.; Raymond, A.K. (International Livestock Research Institute, 2005)
The dairy market in Malaysia is mainly dependent on imported milk and milk products. The demand for milk has increased over the years and is expected to continue to rise with the increase in population and change in lifestyle. In 1990 the self-sufficiency for milk products was 4.66% (DVS, 2005a). Malaysia had, under the 7th Malaysian plan (1999-2000), targeted to achieve 10% self-sufficiency in liquid milk by the year 2000, and 30% by the year 2010. Although it would be unrealistic to expect the local production to meet the total demand, there is need for an increase in production in order to ensure food security and save foreign exchange. This paper reviews one of the many attempts to improve the dairy industry in Malaysia, through development of the Mafriwal dairy cattle by crossbreeding of the Friesian and the Sahiwal breeds.